Inclusion body myositis in an older patient following a fall. Issue 4 (23rd April 2023) - Saiki, Haruma; Isono, Hiroki; Ihara, Kousuke; Kondo, Keisuke; Isono, Momoko; Shiraoka, Akira
Key Clinical Message: After experiencing a fall, an 82‐year‐old woman developed progressive loss of lower limb strength and was diagnosed with inclusion body myositis. Although falls and muscle weakness are often regarded as consequences of aging, inclusion body myositis should be considered in a patient with a history of multiple falls. Abstract : An 82‐year‐old woman was diagnosed with inlcusion body myositis after a fall. Progressive loss of lower limb muscle strenght was also found. Although falls and muscle weakness are often seen as a results of ageing, when a patient has a history of mutiple falls, inclusion body myositis should be suspected.